GÉNESIS Y PRIMEROS PASOS DE LA FACULTAD DE CIENCIAS SOCIALES - Camacho, Daniel (1994)
The article and analyses the historical circumstances in which the Faculty of Social Sciences was created, as well as the purseud intentions of the set going of the institution.